Desain LKPD Berbantuan Canva Melalui Model Discovery Learning Untuk Meningkatkan Kemampuan Literasi Numerasi Siswa Materi Pecahan Kelas ‎IV UPT SD Negeri Kendalrejo 02 - Muhamad Burhanudin; Cindya Alfi; Ragil Tri Oktaviani (Global Action and Education for Society, 2026)
This study addresses the low literacy numeracy skills among fourth-grade students in understanding fractions at UPT SD Negeri Kendalrejo 02. The research aimed to develop and validate a Student Worksheet (LKPD) designed with Canva using the Discovery Learning model to enhance students' literacy numeracy abilities. Employing the ADDIE model, the development process included analysis, design, development, implementation, and evaluation phases. Validity and feasibility assessments were conducted by experts in material, media, and classroom teachers, resulting in validation scores above 90%, indicating the LKPD is highly valid and feasible for use. Implementation involved 20 students, with pretest and posttest results showing significant improvement in literacy numeracy skills; the average pretest score was 65.75, and the posttest score rose to 92.5 with a high N-gain value of 0.76 indicating a substantial increase. The study concludes that LKPD developed with Canva and applied through the Discovery Learning model effectively improves literacy numeracy skills in fraction material, providing an interactive and engaging learning medium. This research contributes to the integration of technology in elementary mathematics learning and supports literacy numeracy development through innovative media.